EFFECTIVENESS OF EU LAW IN MEMBER STATES - ANCA-MAGDA VLAICU (Challenges of the Knowledge Society)
When the original Rome Treaty was drafted, it was envisaged by the authors that the procedure as set out in what is now article 258 T.F.E.U. (infringement procedure) would be the primary means by which EU law is enforced - a “centralized” and “public” form of enforcement assured by the ECJ, the Commission and Member States, which was itself innovative, since most international treaties contained no such mechanism. It was a point of view shared by Member States, who could see no reason why provisions of EC Treaties should be treated any differently from those of other international treaties. Thus, on the one hand, the effect of international treaties was generally governed by the principle that they cannot by themselves create rights and obligations for individuals, but only for contracting states - therefore, states were considered the only ones entitled to claim respect of international norms in international courts (individuals and national courts were excluded); on the other hand, as the text of EC treaties made no specific reference to the effect their provisions were to have, the general rule governing international treaties should also apply to them. The European Court of Justice disagreed and engaged in a prolonged judicial activism, resulting in the creation of other legal mechanisms by which national courts and individuals (rather than ECJ, Commission and Member States) were to take the leading role in the enforcement of EU law - a “decentralized” and “private” form of enforcement, governed by three interrelated principles developed jurisprudentially by the ECJ: direct effect, indirect effect and state liability. In this context, the purpose of this paper is to provide an overview of actual means of EU law enforcement, as presented above; to this end, there will be considered the legal/judicial basis, scope, limits and practical difficulties of the ”centralized” and “decentralized” form of enforcement.